2021
DOI: 10.3390/microorganisms9091860
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacterial Communities of Lymantria xylina and Their Associations with Host Development and Diet

Abstract: The gut microbiota of insects has a wide range of effects on host nutrition, physiology, and behavior. The structure of gut microbiota may also be shaped by their environment, causing them to adjust to their hosts; thus, the objective of this study was to examine variations in the morphological traits and gut microbiota of Lymantria xylina in response to natural and artificial diets using high-throughput sequencing. Regarding morphology, the head widths for larvae fed on a sterilized artificial diet were small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
3
7
2
Order By: Relevance
“…This indicated the larvae of C. medinalis might maintain essentially groups of bacteria residing in the gut. The results in the present study were not entirely consistent with the previous studies to some other lepidopteran insects, L. xylina , S. litura , and H. armigera , with which the dominant bacteria were significantly affected by different diets ( Priya et al, 2012 ; Xia et al, 2020 ; Ma et al, 2021 ). This difference might result from different feeding habits, L. xylina , S. litura , and H. armigera are all highly polyphagous, while C. medinalis is oligophagous, and the larvae are almost only exclusively in rice.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicated the larvae of C. medinalis might maintain essentially groups of bacteria residing in the gut. The results in the present study were not entirely consistent with the previous studies to some other lepidopteran insects, L. xylina , S. litura , and H. armigera , with which the dominant bacteria were significantly affected by different diets ( Priya et al, 2012 ; Xia et al, 2020 ; Ma et al, 2021 ). This difference might result from different feeding habits, L. xylina , S. litura , and H. armigera are all highly polyphagous, while C. medinalis is oligophagous, and the larvae are almost only exclusively in rice.…”
Section: Discussioncontrasting
confidence: 99%
“…With the increased number of insect models used for beneficial gut bacterial studies, there is cumulative evidence that insect gut microbiota play an important role in insect physiology, organ development, protection against natural enemies and help in their nutrition and detoxification. Additionally, they are involved in immune response activation and communication [26][27][28][29][30][31]. Bee gut bacterial communities are not an exception [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that Enterococcus plays an important role for the host, protecting against pathogenic invasion (Grau et al, 2017; M. Ma et al, 2021), and contributing to insecticide resistance (Li et al, 2021; Medina et al, 2018). Thus, Broderick et al (2003, 2004) observed that Lymantria dispar larvae (gypsy moth) were more susceptible to Bacillus thuringiensis (Bt) toxin, also presented a smaller intestinal bacteria population (especially of E. faecalis ) which leads to a decrease in midgut pH.…”
Section: Resultsmentioning
confidence: 99%
“…The insect intestinal microbiota is not only associated with the acquisition of nutrients but plays an important role in the development and maintenance of the host's immune system (Y. Chen et al, 2021; Muhammad et al, 2019). However, the complexity, dynamics, and types of interactions between insects and their intestinal microbiota are not yet fully understood (Q. Ma et al, 2021; Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%